Biosynthesis of copper nanoparticles using Allium eriophyllum Boiss leaf aqueous extract; characterization and analysis of their antimicrobial and cutaneous wound‐healing potentials. (27th February 2020) - Zhao, Hongwei; Su, Haitao; Ahmeda, Ahmad; Sun, Yanqiu; Li, Zongyu; Zangeneh, Mohammad Mahdi; Nowrozi, Masoumeh; Zangeneh, Akram; Moradi, Rohallah
Abstract : Recently, researchers have proven the therapeutic properties of copper nanoparticles as a common product of nanotechnology science. Due to the excellent antioxidant potential of copper nanoparticles, it seems that they can be used for the treatment of infectious diseases and cutaneous wounds. Also, Allium eriophyllum Boiss leaf is used in Kurdish traditional medicine, as one of the popular medicines of the Iranian traditional medicines, for increasing the trend of wound healing. So, we decided to synthesize the copper nanoparticles containing A. eriophyllum leaf aqueous extract, and analyze their potentials in removing bacteria and fungi and healing of cutaneous wounds. After synthesizing the copper nanoparticles, they were characterized with common techniques of organic chemistry, i.e. UV–Vis, Fourier transform‐infrared, X‐ray diffraction, field emission‐scanning electron microscopy (FE‐SEM) and transmission electron microscopy (TEM). For investigating the antimicrobial properties of CuSO4, A. eriophyllum, and CuNPs@ A. eriophyllum, we used the macro‐broth dilation test. Also, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and minimum fungicidal concentration (MFC) of CuSO4, A. eriophyllum, and CuNPs@ A. eriophyllum were gained to indicate the exact antimicrobial potentials of them. To survey the cutaneous wound‐healing effects of CuSO4, A. eriophyllum, and CuNPs@ A. eriophyllum, the 0.2% ointments were formulated and compared with the control and untreated groups. All data of antimicrobial and cutaneous wound‐healing experiments were assessed by SPSS 22 software. The results of chemical characterization indicated that copper nanoparticles had been synthesized as the best form, and the size ranges were 25–35 and 30–35 nm in the FE‐SEM and TEM images, respectively. In the antimicrobial part of this study, CuNPs@ A. eriophyllum indicated higher antifungal and antibacterial effects than all standard antibiotics ( P ≤ 0.01). MIC, MBC and MFC of CuNPs@ A. eriophyllum were 2−4 mg/ml against all fungi and bacteria tested. With regard to cutaneous wound healing, the use of CuNPs@ A. eriophyllum ointment significantly ( P ≤ 0.01) raised the wound contracture, vessel, hydroxyl proline, hexuronic acid, hexosamine, fibrocyte and fibrocytes/fibroblast rate, and significantly ( P ≤ 0.01) decreased the wound area, total cells, neutrophils and lymphocytes compared with other groups in rats. According to the above findings, CuNPs@ A. eriophyllum may be used for the treatment of infectious diseases and cutaneous wounds in humans. Abstract : Investigation of the cutaneous wound healing properties of copper nanoparticles containing natural compounds.